Models for integrating climate objectives in forest policy: Towards adaptation-first? - St-Laurent, G.P.; Locatelli, Bruno; Hoberg, G.; Gukova, V.; Hagerman, S. (Elsevier, 2021)
Recognizing the potential interactions and synergies between adaptation and mitigation in land-use policies in general and forest policies in particular, research on climate change policy has increasingly focused on integrating both objectives simultaneously (hereafter “interaction model”). However, while support exists for the integration of adaptation and mitigation, very few policies have successfully integrated both objectives in practice (hereafter “separation model”). In addition to the interaction and separation models, we introduce the “adaptation-first model”—an approach to climate policy integration that centers adaptation at the core of forest management, with mitigation as one benefit amongst others—and assess whether it more effectively characterizes the practical realities of forest management than the separation or interaction models. Drawing on a review of policy documents, a survey (n = 48) and interviews (n = 22) with government managers in British Columbia (BC), Canada, we analyze which of the three models have been used for integrating climate objectives into BC’s forest policy and explore views of government managers on the relationships and trade-offs between adaptation and mitigation and which model should be prioritized for their integration into forest management. Our analysis of climate-focused forest policy documents indicates that a possible shift from the separation to the interaction model is taking place in BC. However, our results also indicate that while government managers support the interaction model in principle, they perceive numerous barriers to policy integration that may prevent the shift towards the interaction model to materialize in practice. Because of the fundamental perceived differences in the levels at which adaptation and mitigation intervene in decision-making, government managers in our study were generally more comfortable with the adaptation-first model, which ultimately suggests the need to rethink how we frame climate integration into forest management and policies.